DEVELOPING CULTURAL IDENTITY AND PRACTICE IN THE CONTEXT OF TEACHING CHINESE INDIGENOUS DANCE - Wang, Mingquan; Phanlukthao, Peera (International Online Journal of Education and Teaching, 2024)
Education is a process of culturalization in every cultural context since it comprises acquisition and learning. In other sense there are both conscious and subconscious learning process in it. Besides, as the components of the process, there are direct objectives and indirect objectives for the students to attain. Intercultural development in an educational process takes part as both a direct and an indirect component. For example, "Circle dance" is the earliest form of dance created by prehistoric humanity. It is the "living fossil" in the annals of dance culture development. The history of "circle dance" dance culture spans thousands of years. It is enduring, no coincidence, and has been passed down as a result of its singular significance and profound connotation. As a "non-material" art category of the Tibetan and Qiang dance cultures, Tibetan and Qiang ritual dances are non-material in nature. It can begin with its historical development, social function, folk custom function, aesthetic function, historical function, cultural function, and other dimensions when examined in depth. Identifying the shared characteristics and personality development of the "circle dance" dance cultures of Tibetan and Qiang, Tibetan and Qiang performance culture is a vital component of Chinese local culture. As the foundation of the indigenous culture’s identity, emphasize the significance of the Tibetan and Qiang "circle dance" dance culture. Consequently, multiple initiatives can be implemented. The establishment of a cultural research center, a folk culture village, and a cultural museum, Permit the Tibetan and Qiang "circle dance" dance culture to enter the campus, and encourage its new development.